A Novel Design of Energy Management and Control for Smart Microgrids in Urban Buildings - V. Pavan Kumar, Y. (International Journal of Engineering and Technology, 2018)
Microgrids are becoming a popular way to cater the sustaining power needs of urban community loads as buildings of financial districts, universities, industrial zones, gated communities etc. Effective utilization of available energy resources and smart management of operating loads will increase level of supply reliability and reduces the utility grid dependency. With this intent, this paper proposes an original philosophy of designing Smart Energy Management and Control (SEMC) algorithm to transform microgrids as smarter grids. Building microgrid system is modeled using MATLAB/Simulink and is interfaced with real time controller via data acquisition system to form Hardware In the Loop (HIL) setup. This real time controller is realized through Programmable Logic Controller (PLC) by using SEMC algorithm. SEMC manages the available energy sources as well as operating loads based on their availability and priority to supply the total instantaneous load on the microgrid. The proposed algorithm can also facilitate utility grid interaction for import and export of power in deficit and excess available power conditions respectively. From the implementation of the proposed algorithm, the obtained results show that the proposed system ensures reliable and stable supply to building loads.Â Â